The influence of the gut microbiota on B cells in autoimmune diseases - Lun He; Xin Li; Shan Jiang; Yanhua Ou; Shanshan Wang; Na Shi; Zhongshan Yang; Jia-li Yuan; Gregg Silverman; Haitao Niu (Molecular Medicine)
Abstract Mounting evidence shows that gut microbiota communities and the human immune system coexist and influence each other, and there are a number of reports of a correlation between specific changes in gut microbiota and the occurrence of autoimmune diseases. B lymphocytes play a central role in the regulation of both gut microbiota communities and in autoimmune diseases. Here, we summarize evidence of the influence of gut microbiota-B cell pathways on autoimmune diseases and how B cells regulate microorganisms, which provides mechanistic insights with relevance for identification of potential therapeutic targets and related fields.